Identitas Nasional di Persimpangan: Antara Tradisi, Modernitas, dan Globalisasi - Nur Firdaus, Mohammad (Maliki Interdisciplinary Journal, 2025)
Indonesia’s national identity faces significant challenges in the era of globalization, as traditional values and local culture are increasingly eroded by modernity and foreign influences. This study examines the dynamics of Indonesia’s national identity at the crossroads of tradition, modernity, and globalization. The findings indicate that young people are the most vulnerable group to identity crises due to the influence of social media and technology. The main challenges include value shifts, identity crises, and the dominance of foreign cultures. Strategies to strengthen national identity include revitalizing local culture, character education, utilizing technology, strengthening solidarity, and fostering nationalism. Collaboration between government, society, and educational institutions is essential to preserve an adaptive national identity amid global changes.